Board composition and bank performance in a small island developing state: The case of Curacao (2021)
Based on agency theory, this paper contributes to the literature by assessing the effects of Supervisory Board size, gender diversity, and multiple directorship on performance within the banking industry of the small island developing state: Curacao. The research made use of the data drawn from annual reports of locally generated banks and its subsidiaries. Results from linear regressions indicate a positive relationship between multiple directorship and bank performance, and a negative association between bank outcomes and both gender diversity and board size. According to these results, it is concluded that the legislation on corporate governance for credit institutions in Curacao should incorporate a maximum number of members on the board, as well as promote interlocking directorates and quotas by gender.